Medición del Circulante en Dolarización: Ecuador 2000-2007 - Vera L. , Wilson (2007)
The following paper shows the first formal attempt to measure the money supply in the Ecuador from the time when the USD dollar became the official currency in the country. Indeed, since January of 2000 without a local currency and under a dollarized market to estimate the level of money circulating in the economy became a rather difficult task. In; order to measure money supply in Ecuador this paper uses two complementary methodologies: the first one is based on the application of the monetary multiplier methodology while the second one applies a direct estimation based on the amount of USD dollars that the Central Bank requires from abroad to fulfill local necessities as well as the liquidity the financial system holds. Therefore with these parallel procedures it is possible to quantify the liquidity in the nation which is a reference for economic policy, made by the Central Bank itself and by other economic authorities as well.